2013
DOI: 10.1071/rd12139
|View full text |Cite
|
Sign up to set email alerts
|

The role of hypoxia-induced genes in ovarian angiogenesis

Abstract: The hypoxic microenvironment that occurs in fast-growing tissue such as the corpus luteum (CL) is a major contributor to its ability to survive via the induction of an intricate vascular network. Cellular responses to hypoxia are mediated by hypoxia-inducible factor-1 (HIF-1), an oxygen-regulated transcriptional activator. HIF-1, a heterodimer consisting of a constitutively-expressed β subunit and an oxygen-regulated α subunit, binds to the hypoxia responsive element (HRE) present in the promoter regions of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 92 publications
1
47
0
Order By: Relevance
“…Hypoxia is therefore an important physiological cue in the developing CL. It is well established that hypoxia plays an important role in the up-regulation of VEGF that occurs at this stage and is responsible for the angiogenic process in early CL (Tesone et al 2005, Nishimura & Okuda 2010, Meidan et al 2013). The current study shows that the hypoxia-mimetic compound elevated HIF1A protein and EDN2 mRNA levels, whereas HIF1A silencing (employed herein for the first time in GCs) reduced EDN2 expression and ablated its response to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is therefore an important physiological cue in the developing CL. It is well established that hypoxia plays an important role in the up-regulation of VEGF that occurs at this stage and is responsible for the angiogenic process in early CL (Tesone et al 2005, Nishimura & Okuda 2010, Meidan et al 2013). The current study shows that the hypoxia-mimetic compound elevated HIF1A protein and EDN2 mRNA levels, whereas HIF1A silencing (employed herein for the first time in GCs) reduced EDN2 expression and ablated its response to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, HIF-1α can regulate the expression of numerous target genes and play a critical role in many important biological effects, including ovarian functions (Richards et al, 1995;Luo et al, 2011;Zhang et al, 2011aZhang et al, ,b, 2012aMeidan et al, 2013;Wang et al, 2012Wang et al, , 2013Wu et al, 2012Wu et al, , 2013. Moreover, recent studies found that HIF-1α can be regulated by reproductive hormones (Luo et al, 2011;Zhang et al, 2011a,b;2012a,b;Meidan et al, 2013;Wang et al, 2012Wang et al, , 2013Wu et al, 2012Wu et al, , 2013. These studies indicate that HIF-1α is involved in follicular development in the mammalian ovary.…”
Section: Introductionmentioning
confidence: 99%
“…In female rats, 2 pituitary gonadotropin hormones, follicle-stimulating hormone (FSH) and luteinizing hormone, control reproductive cyclical events through different signaling pathways, including follicular development, maturation, rupture, and release of fertilizable oocytes (Richards et al, 1995;Luo et al, 2011;Zhang et al, 2011aZhang et al, ,b, 2012aMeidan et al, 2013;Wang et al, 2012Wang et al, , 2013Wu et al, 2012Wu et al, , 2013. The understanding of the regulatory mechanisms controlling the growth and final differentiation of a mammalian follicle has advanced exponentially, but our understanding of fundamental pathways remains incomplete during these dynamic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Angiogenesis during luteal formation was first observed in early 1990s' (Reynolds et al 1992), and has been the subject of several reviews (Reynolds et al 1994;Redmer and Reynolds 7 1996;Reynolds et al 2000;Meidan et al 2013). VEGF, a potent angiogenic factor, has been first identified in 1989 by Ferarra and Henzel (Ferrara and Henzel 1989), and found to be related to the angiogenesis in the luteal formation in cows (Grazul-Bilska et al 1993) and in women (Kamat et al 1995).…”
Section: Roles Of Hypoxic Signaling In Luteal Formationmentioning
confidence: 99%